A Longitudinal Study on the Effects of Parental Monitoring on Adolescent Antisocial Behaviors: The Moderating Role of Adolescent Empathy - Crocetti, Elisabetta; Van der Graaff, Jolien; Moscatelli, Silvia; Keijsers, Loes; Koot, Hans M.; Rubini, Monica; Meeus, Wim; Branje, Susan (Frontiers in Psychology, 2016)
In adolescence, youth antisocial behaviors reach a peak. Parents can use different strategies, such as parental solicitation and control, to monitor their children’s activities and try to prevent or reduce their antisocial behaviors. However, it is still unclear if, and for which adolescents, these parental monitoring behaviors are effective. The aim of this study was to examine if the impact of parental solicitation and control on adolescent antisocial behaviors depends on adolescent empathy. In order to comprehensively address this aim, we tested the moderating effects of multiple dimensions (affective and cognitive) of both trait and state empathy. Participants were 379 Dutch adolescents (55.9% males) involved in a longitudinal study with their fathers and mothers. At T1 (conducted when adolescents were 17-years-old) adolescents filled self-report measures of antisocial behaviors and trait empathy during one home visit, while their state empathy was rated during a laboratory session. Furthermore, parents reported their own monitoring behaviors. At T2 (conducted one year later, when adolescents were 18-years-old), adolescents reported again on their antisocial behaviors. Moderation analyses indicated that both affective and cognitive state empathy moderated the effects of parental solicitation on adolescent antisocial behaviors. Results highlighted that solicitation had unfavorable effects on antisocial behaviors in adolescents with high empathy whereas the opposite effect was found for adolescents with low empathy. In contrast, neither state nor trait empathy moderated the effects of control on adolescent antisocial behaviors. Theoretical and practical implications of these findings are discussed.